Exploring Barriers to International Trade Faced by Sri Lankan Exporters to the Indian Market - Sumanasiri, Ayoma (Advances in Social Sciences Research Journal, 2021)
In recent decades, India has emerged as a major economy in the world. Although Sri Lanka is situated in close proximity to India and has entered into trade agreements with India to boost its international trade, it has still not been able to achieve the expected level of growth in exports to India. Based on the 2019 United Nations COMTRAD data, India is the third largest export destination of Sri Lanka, and the export revenue from trade with India amounted to US $ 759 million in 2019. However, the statistics in the past years indicate a drop in Sri Lankan export revenue to India from $ 767 million in 2018 to $ 759 million in 2019. In spite of different bilateral and multilateral trade agreements entered into between the two countries, Sri Lankan export performance still remains unsatisfactory. This indicates that apart from tariff reductions, certain other non-tariff barriers influence international trade performance between the two countries. Therefore, this study aims to explore barriers to Sri Lankan exporters which undermine their international trade performance in the Indian market. The study follows a qualitative research methodology and has collected data using face-to-face unstructured interviews with twenty (20) respondents representing different stakeholders engaged in the process of exporting from Sri Lanka to India. The collected data was coded and analyzed through template analysis. Findings revealed thirty-five (35) important factors which influence successful penetration into and performance in the Indian market. The results reveal that host market and home market characteristics have a greater impact on successful performance in the Indian market than product or firm characteristics.